A critical review and analysis of the context, current burden, and application of policy to improve cancer equity in Ghana - Chloe Zabrina Tuck; Richard Cooper; Richmond Aryeetey; Laura A Gray; Robert Akparibo (BMC, 2023)
Abstract Background Cancer causes a major disease burden worldwide. This is increasingly being realised in low and middle-income countries, which account disproportionately for preventable cancer deaths. Despite the World Health Organization calling for governments to develop policies to address this and alleviate cancer inequality, numerous challenges in executing effective cancer policies remain, which require consideration of the country-specific context. As this has not yet been considered in Ghana, the aim of this review was to bring together and critique the social-environmental, health policy and system factors to identifying opportunities for future health policies to reduce cancer burden in the Ghanian context. A critical policy-focused review was conducted to bring together and critique the current health systems context relating to cancer in Ghana, considering the unmet policy need, health system and social factors contributing to the burden and policy advances related to cancer. Conclusion The findings highlight the changing burden of cancer in Ghana and the contextual factors within the socio-ecosystem that contribute to this. Policies around expanding access to and coverage of services, as well as the harmonization with medical pluralism have potential to improve outcomes and increase equity but their implementation and robust data to monitor their impact pose significant barriers.